Effectiveness of High Potassium Diet And Low Sodium on Reducing Blood Pressure in Health Center Of Sokaraja II - Wahyudi Wahyudi; Ani Kuswati; Walin Walin (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
The purpose of the research is to evaluate the effectiveness of high potassium diet and low sodium diet in reducing blood pressure for patients with hypertension. It is a quasi-experimental research with two group pre - post design, the research is conducted in health center of Sokaraja II, Banyumas. A simple random sampling is applied. We divide 28 subjects into 2 categories: 14 subject apply topotasium diet and 14 subject apply sodium diet. The intervension of high potasium diet is by giving the subject 2 Ambon bananas each day for a week. While the low natrium diet is done by giving a tea spoon of salt eaeh day for a week. The results shows that there was no difference between systolic and diastolic blood pressure before and after administration of a high potassium diet, which is the systolic (p value = 0.13) and diastolic (p value = 0.24), low-sodium diet cannot reduce blood pressure significantly (p value = 0.12). However, the diastolic blood pressure is significantly different (p value = 0.001). So, Low sodium diet is more effective in reducing blood pressure in hypertensive patients, especially in diastolic blood pressure compared to a high potassium diet.